Activation studies for the decommissioning of PET cyclotron bunkers by means of Monte Carlo simulations. (September 2020) - Vichi, S.; Infantino, A.; Zagni, F.; Cicoria, G.; Braccini, S.; Mostacci, D.; Marengo, M.
Abstract: During the operational life of a PET cyclotron, the concrete walls of the vault are activated by secondary neutrons. For the dismantling of such accelerator facilities, a considerable amount of low level solid radioactive waste has to be characterized and disposed. To decrease future dismantling costs and complexity, the amount of radioactive waste has to been prospectively evaluated in the design phase, then confirmed at the time of planning decommissioning. In this work, the Monte Carlo code Fluka was used for the assessment of the activation of the bunkers of two different facilities: the 16.5 MeV GE PETtrace at S. Orsola-Malpighi Hospital in Bologna and the 18 MeV IBA Cyclone 18/18 HC at the Bern University Hospital (Inselspital). The simulations were validated by means of experimental measurements performed in our previous works: non-destructive, in field measurements using a portable CZT detector were performed in Bologna; while core drilling samples were extracted from the bunker and measured in laboratory with an HPGe detector in Bern. The activity of the most important radionuclides in the concrete walls of the bunker, namely Eu-152, Mn-54, Co-60, Sc-46, Zn-65 and Cs-134 resulted within the range of 0.01 – 2 Bq/g. The consistency between Monte Carlo results and experimental measurements was within a factor 2 - 3 for most radionuclides, except for Eu-152, Sc-46, Zn-65. The activity concentrations estimated at each position considered exceeds the clearance levels of the new Directive 2013/59/Euratom. The results of this work demonstrate that Monte Carlo simulations based on FLUKA are adequate to assess the residual activation levels, a fundamental information to foresee, plan and optimize the decommissioning of a cyclotron based PET centers. Highlights: The activation in PET cyclotron bunkers was assessed via Monte Carlo simulations. The Monte Carlo code used in this work was Fluka. The model of a GE PETtrace and a IBA CYCLONE with their bunkers was implemented. Monte Carlo simulation results were compared with experimental measurements. The main long lived radionuclides produced were assessed.